Development And Standardization Of A Tool For Patient’s Perception Towards The Physician’s Practices While Prescribing For Radiological Examinations - SURESH SUKUMAR; DR. RAJAGOPAL KADAVIGERE .VENKATACHALAIAH; DR. SABU KARAKKA.MANDAPAM; DR. BINU V S (International Journal of Pharma and Bio Sciences, 2015)
The aim of the research was to develop and standardize a scale to assess patient’s perception on physician’s practices while prescribing for radiological examinations. The study data was collected from May 2013 to January 2014 in Udupi district. The questionnaire for the study was generated based on literature reviews. To assess content expert validation, the generated scale was given to the expert panel. Content validity index (CVI) was calculated using 4 point rater .CVI value of each item ≥0 .83 is considered for the study. To determine the Reliability and exploratory factor analysis the sample size of 10:1 was considered. The tool was administered individually on the subject using rater administered by simple random sampling technique. The internal consistency(IC) of the scale was calculated by considering Cronbach’s alpha values 0.70 and above to be good IC .Exploratory factor analysis (EFA) was carried out to identify the number of underlying factors by keeping factors loading fixed at 0.4 using SPSS15. From our study, 18 items scale was reduced to 15 items by considering CVI value of grater then 0.833. Overall IC for the entire 15 item scale was high with Cronbach’s alpha of 0.835. The outcome of EFA shows two valid factors. The percentage of variability of factor one and two are 50.5 and 16.21.The outcome of the study shows that the standardized scale is potentially reliable and a valid measure tool, in assessing the physician’s practices